2020
DOI: 10.1016/j.arcmed.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus is Associated with Severe Infection and Mortality in Patients with COVID-19: A Systematic Review and Meta-analysis

Abstract: Background and Aim Currently, the number of patients with coronavirus disease 2019 (COVID-19) infection is increasing rapidly worldwide. In this study, we aimed to assess whether diabetes mellitus (DM) would increase the risk of severe infection and death in patients with COVID-19. Methods We systematically searched the PubMed, Web of Science, MedRxiv and COVID-19 academic research communication platform for studies reporting clinical severity and/or overall mortality d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
1
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 91 publications
6
70
1
13
Order By: Relevance
“…Interestingly, a meta-analysis by Miller et al [ 52 ] revealed that the prevalence of diabetes increases the mortality, while comorbidities do not affect the overall number of deaths. The same findings have been observed by Shang [ 53 ], whose team goes as far as to conclude that not only the diabetic patients shall avoid exposure to COVID-19 but also when treated they should be monitored more closely with special attention to improve prognosis.…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, a meta-analysis by Miller et al [ 52 ] revealed that the prevalence of diabetes increases the mortality, while comorbidities do not affect the overall number of deaths. The same findings have been observed by Shang [ 53 ], whose team goes as far as to conclude that not only the diabetic patients shall avoid exposure to COVID-19 but also when treated they should be monitored more closely with special attention to improve prognosis.…”
Section: Discussionsupporting
confidence: 80%
“…As we have shown in this study, other publications have reported that chronic diseases such as diabetes, asthma, hypertension, chronic kid-ney disease, air pollution, and obesity are associated with a high risk of infection and death in COVID-19 patients [10][11][12][13][14][15][29][30][31]. These conditions occur and tend to converge more frequently in older people, but in the middle-aged population (aged 40-55 years) many other possible explanations emerge as to why they are also at high risk of death, when compared with younger persons aged < 40 years, even when they may be free of prevailing chronic diseases.…”
Section: Discussionsupporting
confidence: 73%
“…For instance, the prevalence was reported 68.3% in Saudi Arabia [4] , 33.8% in New York [11] , and 20.9% in Greece [19] . In a meta-analysis, the prevalence of diabetes was 10% in China [20] , and 26.5% in studies outside of China [21] . Likewise, the prevalence of diabetes ranged from 13.0% to 40.2% in multicenter studies reported in similar time frames to our study [10] , [11] , [22] , [23] , [24] .…”
Section: Discussionmentioning
confidence: 98%